The critical thinking skills on animal tissue learning: Inquiry based student activity sheets development - Flaviana Claudia Andayani; Raharjo Raharjo; Widowati Budijastuti (JPBIO (Jurnal Pendidikan Biologi), 2021)
Students' critical thinking skills in Indonesia are still categorized as low, so it is necessary to facilitate learning tools that support critical thinking activities. One of the learning tools is the inquiry-based Student Activity Sheet (LKS) which can train students' critical thinking skills. The purpose of this study was to develop inquiry-based worksheets on animal tissue learning material for class XI SMA Negeri 3 Mojokerto. The model used in this research is the 4-D model, namely define, design, develop and disseminate. The research subjects were 12 students of class XI MIPA 1 as many as 12 students of SMA Negeri 3 Mojokerto. The results of the percentage agreement validation of the LKS were 96% categorized as reliable. The effectiveness of the student worksheet is based on a gain score of 0.89 with high criteria so that the device is said to be effective. Student responses to the developed worksheets obtained results of 99.08% with a very good response. Thus, inquiry-based student worksheets on animal tissue learning material can train students' critical thinking skills.Keywords: Student activity sheet, inquiry model, critical thinking skills, animal tissue